2019
DOI: 10.1101/695759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A co-expression network in hexaploid wheat reveals mostly balanced expression and lack of significant gene loss of homeologous meiotic genes upon polyploidization

Abstract: 14Polyploidization has played an important role in plant evolution. However, upon polyploidization the 15 process of meiosis must adapt to ensure the proper segregation of increased numbers of chromosomes 16 to produce balanced gametes. It has been suggested that meiotic gene (MG) duplicates return to a 17 single copy following whole genome duplication to stabilise the polyploid genome. Therefore, upon 18 the polyploidization of wheat, a hexaploid species with three related (homeologous) genomes, the 19 stabil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 145 publications
(170 reference statements)
0
3
1
Order By: Relevance
“…Thus, on the polyploidisation of wheat, and despite the pre-existence of three ZIP4 copies, duplication and divergence of TaZIP4-B2 was required to promote homologous pairing-synapsis and prevent a potential 50% loss of grain number. These observations contrast with previous studies of polyploid brassicas, which exhibited more extensive chromosome rearrangements and loss of gene content upon polyploidisation [35,36] than is observed in wheat [9]. The absence of the main locus limiting homoeologous recombination in brassicas, BnaPh1 [37], reveals the importance of homoeologous CO suppression for preservation of genome stability in other polyploids.…”
Section: Homoeologous Crossover Suppression By Zip4 Is Not Essential To Maintain Wheat Fertilitycontrasting
confidence: 94%
See 1 more Smart Citation
“…Thus, on the polyploidisation of wheat, and despite the pre-existence of three ZIP4 copies, duplication and divergence of TaZIP4-B2 was required to promote homologous pairing-synapsis and prevent a potential 50% loss of grain number. These observations contrast with previous studies of polyploid brassicas, which exhibited more extensive chromosome rearrangements and loss of gene content upon polyploidisation [35,36] than is observed in wheat [9]. The absence of the main locus limiting homoeologous recombination in brassicas, BnaPh1 [37], reveals the importance of homoeologous CO suppression for preservation of genome stability in other polyploids.…”
Section: Homoeologous Crossover Suppression By Zip4 Is Not Essential To Maintain Wheat Fertilitycontrasting
confidence: 94%
“…Previous studies have revealed extensive chromosome rearrangements in some polyploids leading to changes in gene content and/or expression [3,5,6,7]. However, recent large-scale genome sequencing and RNA analysis has revealed that homoeologous (related) chromosomes of hexaploid wheat ( Triticum aestivum L.) did not exhibit extensive gene loss or expression changes following polyploidisation [8,9]. This suggests that a major factor rapidly evolved upon wheat polyploidisation to control the behaviour of its multiple genomes during meiosis, hence preserving fertility.…”
Section: Introductionmentioning
confidence: 99%
“…This manuscript has been released as a pre-print at (Alabdullah et al, 2019). The authors would like to acknowledge the UK biotechnology and Biological Sciences Research Council (BBSRC; ) for supporting this work.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…KnetMiner is being used extensively to drive gene-trait discovery research in the publicly funded 'Designing Future Wheat' programme (https://designingfuturewheat.org.uk/), see for example (Adamski et al, 2020;Alabdullah et al, 2019;Harrington et al, 2020). Wheat (Triticum aestivum) is the third most-grown cereal crop in the world after maize and rice, and has a hexaploid 15 Gb genome which is 5 times the size of the human genome (The International Wheat Genome Sequencing Consortium Figure 1 Diverse and heterogenous FAIR data sets are harmonized into a knowledge graph using the KnetBuilder software.…”
Section: Gene Network Discoverymentioning
confidence: 99%